2010
DOI: 10.1097/ta.0b013e3181d3cbc0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Is Associated With Improved Outcomes in a Porcine Model of Hemorrhagic Shock

Abstract: : In our porcine model, we found that simulating mild and severe levels of environmental hypothermia during early resuscitation after hemorrhage was associated with a significantly decreased mortality rate. Furthermore, markers of cellular stress and organ dysfunction, including lactate levels and the base deficit, were lower in hypothermic animals. Decreasing oxygen consumption with hypothermia may, in part, explain the protective effects observed with hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
(21 reference statements)
0
32
1
1
Order By: Relevance
“…[7,8] Obviously, it was the unanesthetized model of HS that made experimental results contrary to those of George's. If pigs' normal p h y s i o l o g i c a l r e a c t i o n w a s b l o c k e d u n d e r l o w temperature circumstance, results derived from these animals were not reliable.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…[7,8] Obviously, it was the unanesthetized model of HS that made experimental results contrary to those of George's. If pigs' normal p h y s i o l o g i c a l r e a c t i o n w a s b l o c k e d u n d e r l o w temperature circumstance, results derived from these animals were not reliable.…”
Section: Discussioncontrasting
confidence: 48%
“…[6] In contrast with clinical data, studies in experimental models have consistently showed World J Emerg Med, Vol 3, No 2, 2012 that mild hypothermia induced by surface cooling or intravenous infusion of ice-cold fl uids improves survival during and after HS. [7][8][9] In a previous study, we found that HS model with anesthetized swine was different from that of clinical reality. This might explain the contradiction between experimental studies and clinical scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Induced hypothermia offers a promising approach to attenuating posttraumatic organ damage (19,27). In particular, the microvascular mucosal oxygenation appears to be improved after severe traumatic insults (22,28).…”
Section: Discussionmentioning
confidence: 99%
“…Different experimental studies have shown that induced hypothermia might be able to attenuate the inflammatory response, reduce organ damage, and improve the outcome of severe trauma (17)(18)(19). The important mechanisms associated with these beneficial effects are maintaining aerobic metabolism and reducing oxygen demand (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The mean arterial pressure varies between 20 and 55 mm Hg depending on the examiner and the species. This hypotensive shock state is maintained for 15 min, or in some studies for more than 3 h [53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76](table 3). …”
Section: Types Of Modelsmentioning
confidence: 99%